A conceptual framework for the instructional design of a Moodle-based e-learning course for mainstreaming informal master’s education outcomes into ESP teaching in a formal non-linguistic setting - Larisa M. Galchuk (RUDN Journal of Informatization in Education)
Problem statement. The paper conceptualizes the stages of requirements analysis and content development mandatory in the instructional design of a Moodle-based training course to mainstream master’s informal learning outcomes when teaching English for Specific Purposes (ESP) at a non-linguistic university. The significance of this work lies in the necessity to devise a mechanism for structuring students’ non-institutional learning activities as they engage with their academic discipline within an ICT-supported formal environment, which bears many similarities to contemporary informal learning spaces. Methodology . The research is comprehensive in nature, based on the use of general scientific and empirical methods with the subsequent interpretation of its results in terms of theoretical triangulation. The analysis of existing approaches to integrating the outcomes of informal adult education into the formal context of their lifelong learning has made it possible to develop a conceptual framework for the instructional design of an electronic training course to enhance ESP proficiency of master students. The research algorithm was to analyze the target audience through the prism of their experience in informal language learning with an emphasis on the predominant types of such cognitive activity and preferred information resources; to define the objectives of ESP teaching taking into account the potential for the language development in the informal setting and the affordances of the Moodle-based learning environment; to create a competency model of an electronic course graduate and to develop assessment tools for monitoring and verifying expected outcomes within a formal context. Results . The research highlights the transformation of students’ informal cognitive activities from incidental and accidental learning to conscious and purposeful self-directed learning as a precondition for the successful implementation of a course on integrative mastering of an academic discipline in a formal context and beyond. This involves further development of the master’s systemic competencies and their deliberate transfer from formal to informal educational contexts while working with the learning resources of the lecture and project clusters within the thematic units of the online course. Their multifunctional assignments are crafted to effectively guide students towards productive, independent learning in informal settings, whether through direct, indirect, or subtle cues embedded within the task instructions. Conclusion. The empirical study highlights its practical importance, demonstrating that the proposed instructional design framework for the e-learning course, along with the didactic strategies developed from it, enhances educational content. This is achieved by integrating the outcomes of mastering the academic discipline across both formal and informal learning environments, ensuring cohesion and continuity throughout the educational process.